E-assessment Using Image Processing in ∞Exams - Pathe, Prajakta; Choudhari, Sachin; Gulhane, Monali (International Journal of Computer Sciences and Engineering, 2025)
This paper features a software system called ∞Exams (InfinityExams) which supports (primarily in higher education) paper-based examination and makes it easier, more comfortable and speeds up the whole process while keeping every single positive attribute of it but also reducing the number of negative aspects. The approach significantly differs from the ones used in the previous 10+ years which were implemented in such a way that they could not reproduce and replace the traditional paper-based examination model. The heart of the article relies on the most important element of the software which is the image processing flow.